2005
DOI: 10.1007/s00294-004-0560-2
|View full text |Cite
|
Sign up to set email alerts
|

Salt-dependent expression of ammonium assimilation genes in the halotolerant yeast, Debaryomyces hansenii

Abstract: Debaryomyces hansenii is adapted to grow in saline environments, accumulating high intracellular Na(+) concentrations. Determination of the DhGDH1-encoded NADP-glutamate dehydrogenase enzymatic activity showed that it increased in a saline environment. Thus, it was proposed that, in order to overcome Na(+) inhibition of enzyme activity, this organism possessed salt-dependent mechanisms which resulted in increased activity of enzymes pertaining to the central metabolic pathways. However, the nature of the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In the literature four genes have been reported to be salt-responsive in D. hansenii: DhGPD1, DhENA1, DhENA2 and DhGDH1 (Thomé and Trench 1998;Almagro et al 2001;Guerrero et al 2005). It has been shown that GPD1 in S. cerevisiae is modulated by the HOG pathway and is directly involved in the osmoregulated response in yeasts (Hohmann 2002).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In the literature four genes have been reported to be salt-responsive in D. hansenii: DhGPD1, DhENA1, DhENA2 and DhGDH1 (Thomé and Trench 1998;Almagro et al 2001;Guerrero et al 2005). It has been shown that GPD1 in S. cerevisiae is modulated by the HOG pathway and is directly involved in the osmoregulated response in yeasts (Hohmann 2002).…”
Section: Resultsmentioning
confidence: 97%
“…cerevisiae (Guerrero et al 2005). In the present work DhGPD1 was chosen as a gene marker to study the glycerol response to turgor stress, while DhGDH1 was chosen as a control for the saltresponse in this yeast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Debaryomyces hansenii and Wickerhamomyces anomalus strains were found to be predominantly distributed, whereas Lodderomycese longisporus strains, Zygosaccharomyces bailii, Pichia kudriavzevii, Pichia manshurica, Trichosporonoides spathulata and several unidentified species were subordinated. These yeast species have been isolated from wine or other fermentation processes (6) and studied from the perspectives of metabolism, genetics, and molecular biology (7)(8)(9)(10)(11)(12)(13). Particular stains of Debaryomyces hansenii, Wickerhamomyces anomalus, Pichia kudriavzevii and Pichia manshurica have been found to promote volatile compound formation (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%